Improvement of human sperm properties with platelet-rich plasma as a cryoprotectant supplement - Nabavinia, Maryam Sadat; Yari, Arash; Ghasemi-Esmailabad, Saeed; Gholoobi, Aida; Gholizadeh, Lida; Nabi, Ali; Lotfi, Marzieh; Khalili, Mohammad Ali (Cell and tissue banking, 2023)
Purpose Platelet-rich plasma (PRP) is a remarkable substance, which involves the growth and proliferation of all cell types. As a source of growth factors, we evaluated whether sperm cryopreservation supplemented with PRP improves the rates of sperm motility, viability, and DNA integrity after vitrification compared with conventional cryo-medium. Materials and methods 20 normal semen specimens were collected from healthy men. After swim-up preparation, each sample was divided into four aliquots. One, as control, received no treatment, and the other three experimental samples were treated with three different concentrations of PRP as cryoprotectant. Sperm parameters were examined before and after freezing procedure. Results PRP had no significant effect on sperm count. Meanwhile, the percentage of sperm progressive motility and viability in the PRP treated samples with 1×10 5 /µL concentration was significantly higher than control group. Besides, the rate of immotile sperms in these samples was significantly lower than the control. Sperm viability was significantly higher in the PRP samples at 1×10 5 /µL concentration. In the case of DNA integrity, CMA3 staining showed that the lower PRP concentration was correlated with the higher rate of abnormal spermatozoa. SCD showed that the rate of abnormal sperms in the PRP samples with 1×10 5 /µL concentration was significantly lower than control group. Conclusions This study showed a protective effect of PRP on human sperm quality at an optimized concentration after vitrification. Besides, the effects of PRP supplementation of sperms on successful fertility following sperm preservation will be of interest.